Colti in trappola. L'università postfordista e la formazione del cognitariato - Giuseppe Burgio (Firenze University Press, 2015)
In post-Fordism has now emerged the figure of cognitive workers, who work through communication, symbols and the relationship. Among these should be placed also precarious intellectual workers, that the article fits into the theorist landscape of Italian post-operaism. The analysis deals with the plan of social building and education of precarious cognitive workers. In this perspec-tive, the precarious researchers of Italian universities (PhDs, PostDocs, tem-porary teachers etc.) appear to play a central role because they exploit themself and simultaneously educate cognitive workers of postfordism into submission and obedience. To this aim seems to tend the process of restructuring of the university system.